IMPLEMENTASI KEBIJAKAN PENGELOLAAN BARANG MILIK DAERAH PADA DINAS PENDIDIKAN, PEMUDA DAN OLAH RAGA KABUPATEN SIGI - Nancy, Nancy (Katalogis, 2015)
This research aims at determining the extent of regional ​​property management at the Department of Education, Youth and Sports of District Sigi having been well executed. This research uses a qualitative approach. The determination of research location and key informants was done purposively, with five informants. The obtained data were analyzed progressively based on the data information of the informants that were obtained through observation, interviews and documentation. The result shows that the regional property management at the Department of Education, Youth and Sports of District Sigi is not running well, judging from four aspects (The Use Theory Edward III). This is because the 4 (four) aspects studied explain that the communication aspect shows the lack of socialization implementation, the main source aspect specifies the lack of human resources and budgetary resources, the disposition aspect indicates the lack of responsibility of the manager of the regional property and bureaucratic structure aspect shows the inexistence of SOP of regional property made.